Ca(2+)-induced Ca2+ release in insulin-secreting cells. - Islam, MS; Rorsman, P; Berggren, P (1992)
The sulphydryl reagent thimerosal (50 microM) released Ca2+ from a non-mitochondrial intracellular Ca2+ pool in a dose-dependent manner in permeabilized insulin-secreting RINm5F cells. This release was reversed after addition of the reducing agent dithiothreitol. Ca2+ was released from an Ins(1,4,5)P3-insensitive pool, since release was observed even after depletion of the Ins(1,4,5)P3-sensitive pool by a supramaximal dose of Ins(2,4,5)P3 or thapsigargin. The Ins(1,4,5)P3-sensitive pool remained essentially unaltered by thimerosal. Thimerosal-induced Ca2+ release was potentiated by caffeine. These findings suggest the existence of Ca(2+)-induced Ca2+ release also in insulin-secreting cells.